DOI: 10.17077/etd.fa2gxeel
|View full text |Cite
|
Sign up to set email alerts
|

Arab immigrant Muslim mothers' perceptions of children's attention deficit hyperactivity disorder (ADHD)

Abstract: ADHD is a common behavioral problem among children and adolescents and has been studied extensively. However, this disorder is still understudied in ethnic, immigrant minorities in the U.S. such as Arab families. Thus, this descriptive, qualitative study was important and needed because a gap exists in the literature concerning Arab immigrant mothers' perceptions of the children's behavioral problems such as ADHD and the implications of such child behavioral problems within the Arab immigrant family. The avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 133 publications
(299 reference statements)
0
4
0
Order By: Relevance
“…Mothers of children with attention deficit hyperactivity disorder (ADHD) living in the United States similarly stated that they felt stigmatized. They worried that they would bring shame to their family if they sought help from psychiatrists or psychologists (Al‐Azzam, ).…”
Section: Resultsmentioning
confidence: 99%
“…Mothers of children with attention deficit hyperactivity disorder (ADHD) living in the United States similarly stated that they felt stigmatized. They worried that they would bring shame to their family if they sought help from psychiatrists or psychologists (Al‐Azzam, ).…”
Section: Resultsmentioning
confidence: 99%
“…This study found common challenges faced by parents, such as navigating the complexity of the healthcare and education system, language barriers and social isolation. Such challenges have been identified in previous studies in the United States, the United Kingdom and Canada (Al‐Azzam, 2011; Beatson, 2013; Ijalba, 2016; Khanlou, Haque, et al (2015) and Khanlou, Mustafa, et al (2015); Kwon, 2016; Wang & Casillas, 2012; Zechella & Raval, 2016). Overcoming the difficulties faced by people with disabilities requires interventions such as providing interpreters and the availability of resources necessary to remove environmental and social barriers (WHO, 2001).…”
Section: Discussionmentioning
confidence: 79%
“…This study found common challenges faced by parents, such as navigating the complexity of the healthcare and education system, language barriers and social isolation. Such challenges have been identified in previous studies in the United States, the United Kingdom and Canada (Al-Azzam, 2011;Beatson, 2013;Ijalba, 2016; and Khanlou, Mustafa, et al (2015); Kwon, 2016;Wang & Casillas, 2012;Zechella & Raval, 2016). Immigrant parents raising children with disability shared some similar challenges with non-immigrant parents raising children with disability-social isolation, lack of social support, overwhelming responsibilities, and insufficient understanding of available services are common in these two parent groups (Heather et al, 2006;Murray et al, 2006).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation